Persepsi Warga Lingkungan 21 Kelurahan Tanjung Mulia Tentang Tayangan Infotainment SILET di RCTI - Dilla Arifa; Yan Hendra; Rehia K Isabela Barus (Universitas Medan Area, 2017)
This research is motivated by the presence of Razor Infotaiment on RCTI which is quite popular with the community as entertainment. The purpose of this study was to determine the perceptions of residents of the Environment 21 of Tanjung Mulia Village. The theories used in this study include a description of the theory of mass communication, television mass media, perception, razor infotaiment. The population of this study were residents of the Environment 21 of Tanjung Mulia Village. The sample of this study was 40 people from the Environment 21 of Tanjung Mulia, Medan. The research method used is descriptive quantitative method. The results of the study showed that residents of the Environment 21 regarding Silet infotaiment shows on RCTI were very positive, where people's perceptions of the Silet's infotaiment impressions on RCTI were quite positive when viewed in terms of broadcast material related to the screening schedule, content, time, duration. Likewise from the side of the presenter who brought the infotaiment program.